2019
DOI: 10.1111/jfpe.13324
|View full text |Cite
|
Sign up to set email alerts
|

Millet milk: A comparative study on the changes in nutritional quality of dairy and nondairy milks during processing and malting

Abstract: The effect of different processing like pasteurization, chilling, freezing, cooling and hardening on the protein and fat content of millet milk in comparison to that of dairy milk and plant milk such as coconut milk was studied. When compared to dairy milk, the millet milk showed higher energy (383 kcal) and comparable level of carbohydrates (78%). While the millet milk has higher crude fiber (0.9%) than dairy milk (0.73), it has lesser fiber content than coconut milk (2.26%). Owing to its mineral content, mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Milk extraction from samples was performed using the procedure as described by Nair et al with minor modifications. 15 All samples were weighed and soaked overnight using potable water in a ratio of 1:2, followed by grinding. A 500 W Croma Juicer mixer grinder (model no.…”
Section: Process Of Milk Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…Milk extraction from samples was performed using the procedure as described by Nair et al with minor modifications. 15 All samples were weighed and soaked overnight using potable water in a ratio of 1:2, followed by grinding. A 500 W Croma Juicer mixer grinder (model no.…”
Section: Process Of Milk Extractionmentioning
confidence: 99%
“…Apart from the physicochemical and nutritional profile, it increases the sensory acceptability of millet-milk-based beverages. 15 The combined impact of ultrasound treatment and germination enhances not only the nutritional and sensory profiles but also its antinutrient and in vitro protein digestibility as well. Sharma et al demonstrated the combined effect of germination and ultrasonic treatment of millets and concluded that it increases the protein digestibility and the antioxidants, polyphenols, and GABA concentration in millets.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations